Pengembangan Media Permainan Kartu Unopada Pembelajaran Pendidikan Pancasila PADA Siswa Kelas IV - Lia Utami; Dodik Mulyono; Syaprizal Syaprizal (JOEAI (Journal of Education and Instruction), 2026)
This study aims to develop an engaging and interactive learning media in the form of the Uno card game, resulting in a valid, practical, and effective medium. The research method used was Research and Development (R&D) using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Twenty students participated in the study. The results showed that the developed media was highly valid, with scores for the language validator of 0.93, the media validator of 0.90, and the material validator of 0.90. The average practicality percentage of the media was 94.6%, consisting of 100% individual testing, 95.23% small group testing, and 88.57% teacher response, thus categorizing it as highly practical. In conclusion, the media was proven effective in improving student learning outcomes, as indicated by an increase in the average pre-test score from 53 to 80.5 in the post-test, with an N-gain value of 0.57, which is in the moderate category.   Keywords: Learning Media, Uno Cards, Pancasila Education, ADDIE